Vacancy [compact disc ] - Lennox, Ari (Interscope, 2026)
Grammy-nominated singer Ari Lennox ramps up her 2025 run with the release of her third studio album. With sweet and vivacious tracks ''Soft Girl Era," and vocally vibrant tracks like 'Under The Moon" Ari's step into her divine feminine is expressed throughout the album. This album reflects both an empty space and a new beginning; a recurring theme in Ari's journey. Ari now steps into a new chapter ready to fill the space with a new love, new life, and new experience.